2002
DOI: 10.1159/000067571
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Stapes Superstructure with a Combined Glass-Ceramic (Bioverit<sup>®</sup>) Implant in Guinea Pigs

Abstract: Background: Reconstruction of the stapes superstructure continues to be a problem for otologists. Optimal fixation of implants on the stapes footplate has not yet been achieved. Methods: We postulated that bony fixation, between implant and stapes, could be confined exclusively to the footplate region by modifying the bioactivity of the implant material. Therefore, after removal of the superstructure in guinea pigs a combined biovitro ceramic implant (Bioverit® I and Bioverit® II) was pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Guinea pigs did not show a foreign body reaction to Bioverit Õ I þ II implants in the middle ear [18].…”
Section: Biocompatibilitymentioning
confidence: 84%
See 2 more Smart Citations
“…Guinea pigs did not show a foreign body reaction to Bioverit Õ I þ II implants in the middle ear [18].…”
Section: Biocompatibilitymentioning
confidence: 84%
“…However, only one research group has dealt with a middle ear model of mice for ossicular chain replacements so far [20][21][22]. Dost et al found new bone formation surrounding Bioverit Õ I þ II, hydroxyapatite and Ceravital Õ implants, and also in contact with the middle ear wall in guinea pigs [18,19,23]. Additionally, a significant amount of new bone around the ossicle was observed in a reconstruction with hydroxyapatite cement and dahllite cement [24].…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Merino sheep is a mammal and widely used and established in experimental setups to investigate bone turnover in metabolic bone disease (Sigrist et al 2007) and located fracture healing or integration of prostheses in the skeleton other than the middle ear (Cancedda et al 2007). Adverse mechanisms like the potential of regeneration of ossicular remnants, as known in rodents (Dost et al 2002), were neither reported in literature nor seen in our study. Therefore, we assume our data to be comparable to adult human conditions in metabolic concerns.…”
Section: Discussionmentioning
confidence: 64%
“…Carl et al [13] generated dense non-porous coatings out of Bioverit s I on zirconia. Bioverit s I is a glass ceramic with good bone-bonding ability and long-term stability that has been used for orthopaedic implants [14][15][16][17]. The coatings on zirconia were produced by a sintering process and revealed a good stability and adhesive strength [13].…”
Section: Introductionmentioning
confidence: 99%